2019
DOI: 10.1186/s13229-019-0292-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in neuroligin-3 in male mice impact behavioral flexibility but not relational memory in a touchscreen test of visual transitive inference

Abstract: Cognitive dysfunction including disrupted behavioral flexibility is central to neurodevelopmental disorders such as Autism Spectrum Disorder (ASD). A cognitive measure that assesses relational memory, and the ability to flexibly assimilate and transfer learned information is transitive inference. Transitive inference is highly conserved across vertebrates and disrupted in cognitive disorders. Here, we examined how mutations in the synaptic cell-adhesion molecule neuroligin-3 (Nlgn3) that have been documented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 116 publications
5
24
0
1
Order By: Relevance
“…The decreased perseverative behaviour observed in Nlgn3 −/Y mice during reversal learning in the current study is similar to what we reported previously during a test for visual transitive inference, 40 suggesting heightened sensitivity to non‐reward feedback. Further, the longer response latencies in Nlgn3 −/Y mice observed here are also in accord with similar observations we described in this mutant during the early (A + B − ) stage of the transitive interference test 40 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The decreased perseverative behaviour observed in Nlgn3 −/Y mice during reversal learning in the current study is similar to what we reported previously during a test for visual transitive inference, 40 suggesting heightened sensitivity to non‐reward feedback. Further, the longer response latencies in Nlgn3 −/Y mice observed here are also in accord with similar observations we described in this mutant during the early (A + B − ) stage of the transitive interference test 40 …”
Section: Discussionsupporting
confidence: 91%
“…Therefore, in addition to our key measures of learning, we examined latencies to make correct and incorrect responses, as well as to collect rewards. While most studies employing the touchscreen visual discrimination and reversal learning tasks commonly report latencies pooled across sessions for the whole task (task‐level), we sought to assess latencies at both task (Figures S4 and S5) and session‐by‐session levels (Figures 4 and 5) as we have previously seen response latencies, but not reward collection latencies, alter with the progression of testing on tasks 18,40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant and transgenic mouse models of ASD are engineered using different background strains (JAX SFARI website) and these background strains differ in their behavioral phenotypes 68,69 . For example, NRXN and NLGN mouse models of ASD have been constructed on the C57BL/6J background, 57,70‐ the C57BL/6NCrl background, 72 the 129s6/SvEvTac/C57BL6J background 73 ; the Sv129/C57BL6 background 56 and the 129S2/SvPasCrl background 74 . Host genetic backgrounds themselves can influence diverse neurological responses.…”
Section: Introductionmentioning
confidence: 99%
“…Dichas mutaciones se han asociado con el desequilibrio excitatorio/ inhibitorio característico del autismo y la epilepsia, donde se encuentran conexiones cerebrales menos inhibidas (1,81,82). En ratones, la sobreexpresión y la eliminación de las Nlg lleva a deficiencias en la interacción social o la comunicación, a comportamientos repetitivos, a ansiedad y a problemas de aprendizaje y memoria (83,84). En Drosophila, el KO de dnlg2 produce una disminución en los botones sinápticos, desarrollo aberrante de las uniones neuromusculares y una transmisión sináptica afectada; en tanto que los receptores de glutamato están disminuidos y hay una reducción de los potenciales de unión excitatoria.…”
Section: Neuroliginasunclassified